Successful Sirolimus Treatment for Recurrent Pericardial Effusion in a Large Cervicomediastinal Provisionally Unclassified Vascular Anomaly: A Case Report - Moreno-Alfonso, Julio César; San Basilio Berenguer, María; Sarmiento Caldas, María del Carmen; González Cayón, Jesús; de la Puente, Santiago; Triana, Paloma; López-Gutiérrez, Juan Carlos (European Journal of Pediatric Surgery Reports, 2023)
Provisionally unclassified vascular anomalies (PUVA) are a group of diseases with unique characteristics that make them unclassifiable within vascular tumors or malformations. We describe a PUVA as the cause of recurrent pericardial effusion and its response to sirolimus. A 6-year-old girl was referred with a cervicothoracic vascular anomaly, a violaceous, and irregular lesion in the neck and upper chest, diagnosed as “hemangioma”. She had pericardial effusion at the neonatal age that required pericardiocentesis, propranolol, and corticosteroids. She remained stable for 5 years, when she presented with a severe pericardial effusion. A magnetic resonance visualized a diffuse vascular image in the cervical and thoracic region with mediastinal extension. The pathological study showed a vascular proliferation in the dermis and hypodermis with positive staining for Wilms' Tumor 1 Protein (WT1) and negative for Glut-1. Genetic testing found a variant in GNA14, for which the diagnosis of PUVA was established. When a pericardial drain was placed without response, treatment with sirolimus was started with resolution of the effusion. Sixteen months later, the malformation is stable and there has been no recurrence of pericardial effusion. In a significant group of patients, definitive diagnosis is not possible despite pathological and genetic analysis. Mammalian target of rapamycin inhibitors may become a therapeutic option if symptoms are severe enough, with a low rate of reported side effects.
Keywords: vascular malformations; provisionally unclassified vascular anomaly; sirolimus; pericardial effusion; case report